Pile response subjected to rock blasting induced ground vibration near soil-rock interface - Jayasinghe, Laddu Bhagya (2017)
Blasting has been widely used in mining and construction industries for rock breaking. Ground vibration induced by blasting is an inevitable side effect that may cause damage to nearby structures, if not properly controlled. In this study, response and possible damage of rock-socketed pile near soil-rock interface subjected to ground shock excitations are investigated and quantified with coupled SPH-FEM method. Results indicate that the base of the pile is relatively vulnerable and that the soil properties significantly influence on response of pile subjected to a specific blast load. Furthermore, based on the numerical results, ground vibration attenuation equation is proposed.